From pilot to national roll-out of the improved Community Health Fund (iCHF) in Tanzania: lessons learnt and way forward - Ntuli A. Kapologwe; Boniphace Marwa; Heri Marwa; Ally Kebby; James Tumaini Kengia; George Ruhago; Stephen M. Kibusi; Innocent B. Mboya; Gemini Mtei; Albino Kalolo (Cost Effectiveness and Resource Allocation)
Abstract Introduction Scaling up public health interventions in the health systems of resource poor settings come with technical and operational challenges. Little is documented on scaling up complex health financing interventions and their related outcomes, especially the voluntary health insurance schemes. This study aimed to analyse the scale-up steps, successes and challenges of the improved community health fund (iCHF), a voluntary health insurance scheme in Tanzania, Methods In this paper, guided by the Expand Net framework (a scale-up framework for health system interventions), we present a systematic analysis of countrywide scale-up of the iCHF that started in 2019 and implemented in partnership between the government and development partners. We systematically collected information on the scale-up steps and the success and challenges. The collected data was analysed using descriptive statistics. Results The scale-up involved multiple steps and actions at different levels of the health system. The initial step involved gathering stakeholders’ views on scale-up options and strategies. The subsequent steps focused on mobilizing resources for scale-up, advocacy and promotion of the scheme through media, community leaders and role models, capacity building to implementing organs, institutionalizing the scale-up processes, intensifying the scale-upscale-up activities for expansion and spontaneous scale-up and technical backstopping to lower levels of the health system on the scale-up process. We found success and challenges as the scale-upscale-up progressed to mature stages. The success included acceptability and institutionalization of the scale-up activities and growing enrolments and funds in the scheme. The challenges included: the costs to sustaining advocacy and enrolments, equity in scale-upscale-up activities across regions, relying on top-down scale-upscale-up approaches, influence of contextual factors and lack of implementation research alongside the scale-upscale-up process. Conclusion This paper underscores the scale up steps and success and challenges of scaling-up a voluntary health insurance scheme in a resource-constrained health system. Sustaining the scale-upscale-up gains will require utilizing program data and experiences to sustainably improve the scheme performance while also harnessing support from stakeholders. Further research is needed to assess equity and quality of outcomes of the scale up.